Analisis Penyelesaian Sengketa terhadap Upaya Pengambilalihan Hak atas Tanah Adat di Wilayah Kampar, Provinsi Riau - Samuel Siahaan; Al Fatih Muhammad Azlan; Grace Shalomitha Lova Sibarani; Lolyta Shalin Sihombing; Tara Yohana Panjaitan; Muhammad Raihan Ghafari; Tufel Muhammad; Nurahim Rasudin (Pusat Riset dan Inovasi Nasional, 2025)
Customary land is an integral part of the identity and survival of customary law communities, including in the Kampar region, Riau Province. However, along with increasing investment and development, there have been various forms of takeover of customary land rights that have triggered disputes between customary communities and third parties, such as private companies and the government. This study aims to analyze the mechanism for resolving disputes over the takeover of customary land rights in the Kampar region using customary law and national law approaches. The method used is a combination of normative and empirical juridical, data obtained through legal document studies, interviews with authorized local customary leaders. The results of the study show that customary communities in Kampar still rely on customary resolution mechanisms. Meanwhile, in resolving litigation, they often experience administrative and economic obstacles, while non-litigation channels such as multistakeholder mediation and administrative recognition by the local government are more effective if supported by policies that support them. In conclusion, synergy between customary law and national law is absolutely necessary to create fair protection for the rights of indigenous peoples, and it is hoped that there will be strengthening of customary institutions, acceleration of recognition of customary areas through regional regulations, and preparation of integrated mechanisms for resolving disputes based on local culture and national legal certainty.